Correlation of Glycated Albumin Levels and the Glycated Albumin/HbA1c Ratio with Diabetic Retinopathy - Riswan Hadi Kusuma; Windarwati Windarwati; Budi Mulyono (Academic Hospital Journal, 2026)
Background: Diabetic retinopathy is one of the microvascular complications of Diabetic Mellitus (DM). Diagnosis of diabetic retinopathy based on clinical manifestations of retinal vascular disorders, assessed using the Early Treatment Diabetic Retinopathy Study (ETDRS) severity scale. Fluctuations in blood glucose levels are thought to play a role in the progression of DM complications, and glycated albumin appears to reflect greater fluctuations in blood glucose levels. The aim of this study was to determine the difference and correlation between glycated albumin levels and glycated albumin/HbA1c ratio (GA/HbA1c ratio) with the degree of severity of diabetic retinopathy.Methods: The research design was cross-sectional. The subjects of the study were DM patients who were examined for glycated albumin, HbA1c, and GA/HbA1c ratio calculation, and for clinical examination of retinal vascular disorders using the ETDRS severity scale.Result : The median glycated albumin level in the non-diabetic retinopathy group was lower than the diabetic retinopathy group (18.8 vs 24.3; p=0.018), while the median GA/HbA1c ratio appeared to be lower than the diabetic retinopathy group but did not differ significantly (2.4 vs 3.4; p=0.238). The level of glycated albumin and the GA/HbA1c ratio did not appear to be linear with the severity of diabetic retinopathy. There was a significant weak positive correlation between glycated albumin levels and diabetic retinopathy (r=0.304; p=0.006), while the correlation between the GA/HbA1c ratio and diabetic retinopathy was not significant (r=0.218; p>0.176).Conclusion : There is a significant difference in glycated albumin levels between non-diabetic non-retinopathy and diabetic retinopathy. There is a significant positive correlation between glycated albumin levels and diabetic retinopathy. It needs further study with a larger sample and a balanced distribution of non-diabetic retinopathy and diabetic retinopathy groups to be used independently.